2016
DOI: 10.1002/mrc.4391
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the surface affinity of water in three biochars using fast field cycling NMR relaxometry

Abstract: Many soil functions depend on the interaction of water with soil. The affinity of water for soils can be altered by applying soil amendments like stone meal, manure, or biochar (a carbonaceous material obtained by pyrolysis of biomasses). In fact, the addition of hydrophobic biochar to soil may increase soil repellency, reduce water-adsorbing capacity, inhibit microbial activity, alter soil filter, buffer, storage, and transformation functions. For this reason, it is of paramount importance to monitor water af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 31 publications
(70 reference statements)
0
25
0
1
Order By: Relevance
“…In fact, while CA provides only macroscopic wettability, NMR relaxometry allows a description of the mechanisms for water molecular dynamics on biochar surfaces, thereby leading to the possibility of understanding the role of biochar in increasing soil quality and plant nutrition. In fact a bimodal distribution of water molecules experiencing different environments was identified in each biochar/water mixture [34]. The narrow distribution of water molecules centered about T 1 $ 2.5 s is due to the oxygen dissolved in bulk water.…”
Section: Surface Affinity Of Water In Biocharsmentioning
confidence: 95%
See 3 more Smart Citations
“…In fact, while CA provides only macroscopic wettability, NMR relaxometry allows a description of the mechanisms for water molecular dynamics on biochar surfaces, thereby leading to the possibility of understanding the role of biochar in increasing soil quality and plant nutrition. In fact a bimodal distribution of water molecules experiencing different environments was identified in each biochar/water mixture [34]. The narrow distribution of water molecules centered about T 1 $ 2.5 s is due to the oxygen dissolved in bulk water.…”
Section: Surface Affinity Of Water In Biocharsmentioning
confidence: 95%
“…their wettability) when addressing their applications in soil systems. Bubici et al found that either NMR or contact angle (CA) results revealed the same wettability trend for the biochars they studied [34]. However, the advantage of NMR relaxometry over CA measurements lies in the possibility of obtaining a variety of different information at the microscopic level in a single experiment.…”
Section: Surface Affinity Of Water In Biocharsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is possible that this characteristic is attenuated with the breakdown of hydrophobic compounds with the "aging" of the biochar (TEIXEIRA et al, 2017). Even with contradictory results, the addition of biochar in the soil still denotes promising responses, such as better soil structuring and decreased soil density (BUBICI et al, 2016;TEIXEIRA et al, 2017). In addition to increased crop productivity and soil fertility (CARVALHO et al, 2014).…”
Section: Resultsmentioning
confidence: 99%